Simple Practical Design of Making Purple Cabbage Indicator Paper as Acid-Base Indicator in Chemistry Learning - Salutri*, Gesa; Muna, Laili Nailul; Pusfitasari, Dewi Vitama (Universitas Syiah Kuala, 2025)
The curriculum is the basis for implementing the learning activity method, and the practicum method can be one way to achieve learning outcomes. The acid-base practicum learning method in chemistry learning uses indicators to identify acid-base compounds. The indicator that can be used is the use of natural materials with purple cabbage. Purple cabbage has a distinctive color, namely purple, which is caused by the presence of a color pigment, namely anthocyanin. This study is a qualitative descriptive study with data collection techniques of triangulation data (literature study, observation, and experiment). This study aims to optimize the manufacture of indicator paper from purple cabbage, and to analyze the feasibility of its application experiment through curriculum analysis and learning outcomes. The methods used are maceration, anthocyanin test, indicator paper success test, indicator paper stability and durability test and analysis of learning outcomes. The results obtained are that purple cabbage indicator paper can be used to identify acids and bases effectively, especially strong acid and strong base compounds and can be used in chemistry learning to achieve learning outcomes. The stability and durability test of purple cabbage indicator paper can be used for 15 days of storage at room temperature.